2000
DOI: 10.1111/j.1432-0436.2000.660408.x
|View full text |Cite
|
Sign up to set email alerts
|

Embryonic, fetal, and neonatal tongue myoblasts exhibit molecular heterogeneity in vitro

Abstract: Variable gene expression patterns have been shown to exist between embryonic, fetal, and neonatal lineages of limb skeletal myoblasts in vitro and in vivo. In this study, we examined the molecular phenotype of embryonic, fetal, and neonatal tongue myoblasts in primary culture for comparison with in vivo developmental tongue myoblasts. Myogenic regulatory factor (MRF) and myosin heavy chain (MHC) gene expression were determined in culture during both growth and differentiation conditions by PCR, immunoblotting,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…In both avian and murine embryos, tongue and laryngeal muscle precursors maintain myf5 expression throughout their ventral movements; appendicular myogenic cells do not (Bladt et al, 1995;Dalrymple et al, 2000;Mackenzie et al, 1998;Noden et al, 1999).…”
Section: Differentiation and Compartmentalization In Somitesmentioning
confidence: 99%
“…In both avian and murine embryos, tongue and laryngeal muscle precursors maintain myf5 expression throughout their ventral movements; appendicular myogenic cells do not (Bladt et al, 1995;Dalrymple et al, 2000;Mackenzie et al, 1998;Noden et al, 1999).…”
Section: Differentiation and Compartmentalization In Somitesmentioning
confidence: 99%
“…Thus, we characterized the expression GFP in several muscle and non‐muscle tissues and organs from adult FastTnI/GFP mice (>2 months old), both in western blots and by fluorescence microscopy. The skeletal muscles studied were the Soleus (a slow‐twitch oxidative muscle enriched in type I slow fibers), the Extensor Digitorum Longus (EDL), the complex Gastrocnemius‐Plantaris (GP) and the Diaphragm (all three being fast‐twitch glycolytic muscles composed mainly of variable amounts of IIA, IIB and IIX fast fibers), as well as the tongue musculature (uniformly composed of fast fibers in mouse (Dalrymple et al ., ; Shuler and Dalrymple, ). The heart was also examined as another type of muscle, while the brain, liver and spleen were assessed as non‐muscle organs (Fig.…”
Section: Resultsmentioning
confidence: 94%
“…Since it was first shown that the muscle fibers of mouse tongue consisted entirely of fast isoforms of MyHC (Dalrymple et al, 1999(Dalrymple et al, , 2000Shuler and Dalrymple, 2001), the composition ratio for each isoform has been studied in detail using gel electrophoresis (Agbulut et al, 2003). These studies have indicated that although MyHC-2b continues to increase after birth, MyHC-2a is expressed only transiently for several weeks postpartum.…”
Section: Discussionmentioning
confidence: 99%
“…Previous investigations have shown that tongue muscle consists of fast MyHC 4 isoforms (Dalrymple et al, 1999(Dalrymple et al, , 2000Shuler and Dalrymple, 2001). Agbulut et al determined MyHC composition ratios in mouse tongue muscle and reported that while MyHC-2b increases from birth onward, MyHC-2a is expressed transiently, for only a few weeks postpartum (Agbulut et al, 2003).…”
Section: Introductionmentioning
confidence: 99%